The evolution of management of type B aortic dissection in a series of 100 consecutive cases in a tertiary center - Lopes, Alice (2023)
© 2023 Published by Elsevier Espa˜na, S.L.U. on behalf of Sociedade Portuguesa de Cardiologia. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).